2013
DOI: 10.4274/jcrpe.1060
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism Masquerading as Rickets: Diagnostic Challenge and Treatment Outcomes

Abstract: Primary hyperparathyroidism (PHPT) is extremely uncommon among children and is more likely to be associated with genetic syndromes, multiglandular involvement, and more severe symptoms. Rickets can very rarely be the presenting feature of PHPT in children. Rickets was diagnosed in a 12-year-old girl presenting with short stature, genu valgum, eversion deformity at the ankle joints, and flat feet. Radiograms showed generalized osteopenia, widening of the distal ends of the long bones along with splaying, cuppin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…In pediatric and juvenile PHPT, there is more extensive and severe musculoskeletal involvement. Primary hyperparathyroidism may masquerade as rickets in children and adolescents which has earlier been reported in a few case reports [4][5][6][7][8][9]. In our cohort, 50% patients presented with rachitic manifestations with genu valgum being the most predominant phenomenon.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In pediatric and juvenile PHPT, there is more extensive and severe musculoskeletal involvement. Primary hyperparathyroidism may masquerade as rickets in children and adolescents which has earlier been reported in a few case reports [4][5][6][7][8][9]. In our cohort, 50% patients presented with rachitic manifestations with genu valgum being the most predominant phenomenon.…”
Section: Discussionsupporting
confidence: 63%
“…The literature on pediatric PHPT is so far limited to a few case reports and case series [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the case reported by Dutta et al . [ 1 ] their patient also had a single adenoma. In all our three children there was a single adenoma.…”
Section: Discussionmentioning
confidence: 98%
“…Rickets as presenting feature of PHPT in children is extremely rare with only 23 cases reported till date. [ 1 2 ] PHPT is typically a disease of post-menopausal women in Caucasian population. However, in areas of vitamin D deficiency and calcium deficiency, PHPT may be seen in young patients and even in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 31 , 32 There have been cases reported that primary hyperparathyroidism could masquerade as rickets, especially in childhood or in adolescence. 33–35 The possible explanation is that atypical clinical manifestations of FHH may coexist with vitamin D deficiency, and might be further aggravated by elevated PTH levels. Moreover, there may be deleterious effect of continuously high level of PTH that acts directly on chondrocytes.…”
Section: Discussionmentioning
confidence: 99%